Polityka rządu w zakresie wspierania działalności innowacyjnej polskich przedsiębiorstw (Świat Idei i Polityki, 2014)
Innovation policy plays an important role in the innovation of Polish companies. The main objective of this article is to present the importance of government policy in promoting innovation within Polish enterprises and companies. To accomplish the main objective was to contribute specific objectives, which were present tools or the implementation of the innovation policy by the state companies, and the results of their implementation. This article consists of two parts, the theoretical, in which the author presents the scope of implementation of government policy tools to support innovation of Polish companies, and empirical, which offers a description of results of this policy's implementation. Results of implementation of the state policy in the field of innovation of Polish companies provide proof of the article's thesis that the state policy has a significant impact on the level of innovation in Polish companies.